Interpreting People Interpreting Things: A Heideggerian Approach to ‘Experimental Reconstruction’ - Steve Townend (Papers from the Institute of Archaeology, 2002)
This paper represents some preliminary thoughts on what one area of experimental archaeology might begin to look like if approached through the early philosophy of Martin Heidegger. The broader remit of this research seeks to re-draw experimental archaeology as a practice that is understood for its ‘interpretative’ character rather than as narrowly ‘scientific’ as conventionally portrayed. The specific subject of this paper is a development of Heidegger’s notion of ‘skilled coping’ and the relationship between people and things in the context of the physical reconstruction of the later prehistoric roundhouse in Britain. In this paper I will argue that understandings of the reconstruction and construction of the later prehistoric roundhouse may be significantly enhanced by examining them in relation to a series of phenomena interpreted from the early work of Martin Heidegger. This perspective is intended to re-conceptualise the way in which reconstruction as an exercise is theorised by centring such projects on their human element. It gives practitioners a range of phenomena to consider or include in their research aims and projects that are other to the normal considerations of technology, material constraints, etc. In so doing it will be possible to counter some of the failings of experimental archaeology. This approach is seen as an augmentation to current theory and practice. It aims to make a broader contribution to the theory, practice and role of other ‘field-based’ or replicative experiments and to understandings of a human element that has been largely unexplored within experimental archaeology.
Keywords: Heidegger; Experimental Archaeology